Evaluación de los animales en base a los caracteres de importancia económica en la producción de leche de bovinos acorde al objetivo de mejora genética en la parroquia Pastocalle. - Asimbaya Caiza, Kevin Fabricio (2023)
Into Ecuador, barely a 20% corresponds to the large milk producers, the majority are medium and small farmers. Currently, within the country, they are pioneers in a genetic improvement real program development into dairy cattle, which it is developed by the Cotopaxi Technical University, the same is within the province, it seeks to help the medium and small producer, though gathering information, selection of reproducers and artificial insemination into bovines, this together with advice for the producer to improve the administration their stockbreeding, resolve doubts about the management and achieve for getting profitable milk production. In the Cotopaxi province, Latacunga city, in the Pastocalle parish, where it is based the genetic improvement project, in the research it was included to 131 bovines, from 14 producers, who were contacted in order to carry the project following phase, in order determine and discuss the different key points, when it comes to artificial insemination. Additional to this, it continued the different breeds identification, due to this is the main selection character, within these, it can mention: Holstein 53,4%, Jersey 18,3%, Montbeliarde 8,4%, Brown Swiss 7,6%, Norman 4,6%, Pizan 2,3%, Girolando 1,5%, Angus x Montbeliarde 0,75, Angus x Swedish Red 0,75%. Into together with the different characters analysis, such as the animal`s weight, the milk production assessment (density, weight, CMT), they allow to identify possible problems, regards as management. Within the sector, the aim at improvement is to reach a weight 500gr/day gain, in the milk weight to reach 1, 03 kg/lt, and what is within the reproductive state is to achieve that the sector has an 85% pregnancy, therefore, it has been selected 4 females, which reach to a referential values approximate, these with the purpose, it can disseminate their genetics and to maintain the selected characters.